RPL13A and EEF1A1 Are Suitable Reference Genes for qPCR during Adipocyte Differentiation of Vascular Stromal Cells from Patients with Different BMI and HOMA-IR - Gentile, Adriana Mariel; Lhamyani, Said; Coín-Aragüez, Leticia I.; Oliva Olivera, Wilfredo; Zayed, Hatem; Vega-Rioja, Antonio; Monteseirin, Javier; Romero-Zerbo, Silvana Yanina; Tinahones-Madueño, Francisco José; Bermúdez Silva, Francisco Javier; El-Bekay, Rajaa (Public Library of Science, 2016)
Real-time or quantitative PCR (qPCR) is a useful technique that requires reliable reference genes for data normalization in gene expression analysis. Adipogenesis is among the biological processes suitable for this technique. The selection of adequate reference genes is essential for qPCR gene expression analysis of human Vascular Stromal Cells (hVSCs) during their differentiation into adipocytes. To the best of our knowledge, there are no studies validating reference genes for the analyses of visceral and subcutaneous adipose tissue hVSCs from subjects with different Body Mass Index (BMI) and Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) index. The present study was undertaken to analyze this question. We first analyzed the stability of expression of five potential reference genes: CYC, GAPDH, RPL13A, EEF1A1, and 18S ribosomal RNA, during in vitro adipogenic differentiation, in samples from these types of patients. The expression of RPL13A and EEF1A1 was not affected by differentiation, thus being these genes the most stable candidates, while CYC, GAPDH, and 18S were not suitable for this sort of analysis. This work highlights that RPL13A and EEF1A1 are good candidates as reference genes for qPCR analysis of hVSCs differentiation into adipocytes from subjects with different BMI and HOMA-IR.
Keywords: Obesidad; Adipogenesis; Real-time or quantitative PCR (qPCR); EEF1A1; RPL13A; Obesity